Analysis for Wind Characteristics in Teluk Kalung, Kemaman, Terengganu - Muhammad Hisyam, Abdullah; Mohamad Idris, Ali; Ngien, S. K. (Scientific Research Forum, 2016)
Wind characteristics namely wind speed and direction are very important in the determination of air pollutant concentration. The industrial development in Teluk Kalung which has been expanding every year definitely will further increase the load of air pollution to the nearby area. Sampling of wind data in 2015 at the sampling station about 2 km away from the nearby industrial area in Teluk Kalung was collected in this study. The wind rose analysis found that the dominant wind direction was blowing from the North, Southeast and Northwest. Wind speed was blowing at the speed of below 3.5 m/s which was at the level of light and calm winds with percentages above 50% and most occurred during nighttime. Keywords: Wind rose, wind direction, wind speed, pollutant, air pollution.